The informal economy of the habal-habal motorcycle taxi in the province of Aklan. - Legaspi, Bob Audusto F.
The habal-habal operations in Aklan are not only a widely-used transportation mode but also a comon source of livelihood especially in far-flung communities. However , they lack regulation and protection as they are not acknowledge by the Land Transportation of the Philippines. This study aimed to create an overview and describe the socio economic profile of the drivers of the 'habal-habal' motorcycle taxi operations in the province of Aklan. A descriptive anlysis as well as regression and cost-returns analysis was conducted for this purpose. A structured interview was conducted at random on 170 drivers which are spread equally in 10 municipalities of respondents. Results showed that the drivers are all males with a mean age of 35 and earn below the minimum wage with an average gross earnings per week of 2464.82 PHP. It is found that the operations are risky suggested by the high incidence of accidents, aand carrying passengers beyond the passenger capacity and several cases of driving without license.